PUDING LIDAH BUAYA MENGURANGI KEPUTIHAN PADA WANITA USIA SUBUR KADER KESEHATAN ‘AISYIYAH DUKUH WALUH - Margiana, Wulan; Muflihah, Ima Syamrotul (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2019)
In Indonesia, about 90% of women have the potential to experience vaginal discharge because the country of Indonesia is a tropical climate, so mushrooms are easy to grow and develop which results in many cases of vaginal discharge in Indonesian women (Nurul et al. 2011). The number of women in the world who have experienced vaginal discharge is 75%, while European women who experience vaginal discharge are 25%. In Indonesia as many as 75% of women have had vaginal discharge at least once in their lives and 45% of them can experience vaginal discharge twice or more (BKKBN, 2011). The purpose of the service is to increase the knowledge and skills of cadres ‘Aisyiyah Hamlet Waluhi in dealing with vaginal discharge problems in women of childbearing age. Community service was attended by 19 cadres ‘Aisyiyah Dukuh Waluh. The method used is Learning by doing through lectures, discussions, making leaflets, and role play. After counseling about aloe vera pudding reduced leucorrhoea in women of childbearing age there was an increase in knowledge to cadres ‘Aisyiyah Dukuh Waluh about aloe vera pudding reduced leucorrhoea in women of childbearing age and there was an increase in leucorrhoea skills. Keywords: Aloe vera, leukorrhea